Amenities for Encouraging Ecotourism in Diyawanna Area - Ruzaik, Fareena (Excellent Publication, 2021)
Diyawanna Oya is located 11 km away from the city of Colombo. It is an ecologically and historically important water body, which flows through the current administrative capital of Sri Jayawardanepura Kotte. It has a long history, since the regime of King Parakramabahu VI, and it is also a great significance wetland, covered with verdant fields and evergreen vegetation with rich biodiversity. Therefore, it is an important environment for wildlife and to develop recreational benefits, such as exercise, sports and family outings, fishing, cattle grazing, collecting reeds, rushes and fuel wood for the general public. Further, it provides important hydrological services and is a rich habitat for a wide variety of fauna and flora. Accordingly, the Diyawanna Oya wetlands contribute significantly to the social well-being of the surrounding urban and sub-urban environment, as well as the communities. As a result, the Department of Wildlife declared Diyawanna Oya as a “bird sanctuary" in terms of the Fauna and Flora Protection Ordinance (section No 1 of 1994,) and subsequent Gazette notification.
Keywords: Diyawanna Oya; Biodiversity; Sri Lanka